PROMOTING LITERACY SKILLS THROUGH STORYBIRDS AS WEB-BASED TECHNOLOGY - Lestari Setyowati; Sony Sukmawan; Ana Ahsana El-Sulukkiyah (Universitas Muhammadiyah Ponorogo, 2019)
In this 21st century era, technology plays a significat role in language teaching and learning process both inside and outside the classroom This study is intended to describe the language education lecturers’ opinion and the students’ opinion on the use of storybird as web-based technology for literacy skills by using case study design. The subjects of the study were the language education lecturers and the students who joined writing class in STKIP PGRI Pasuruan in the academic year 2018-2019. The instruments used were interviews and document analysis. Three findings are revealed from the study. Firstly, 81% of the language lecturers used web-based technology for their teaching, but only very few of them were familiar with storybird platform. These lecturers agreed that storybird was beneficial to sharpen the students’ literacy skill. Secondly, the majority of the students (73%) believed that the use of storybird helped them to write better. Two appealing aspects of storybird which encouraged students to read and write were its beautiful pictures and its freedom for everyone to use, while the weakness laid in the requirement to be online and the difficulty to download the story.